Cover Image. Issue 9 (September 2016) - DebRoy, S.; Hiraga, N.; Imamura, M.; Hayes, C. N.; Akamatsu, S.; Canini, L.; Perelson, A. S.; Pohl, R. T.; Persiani, S.; Uprichard, S. L.; Tateno, C.; Dahari, H.; et al.
Abstract : The cover image, by Kazuaki Chayama et al., is based on the Original Article Hepatitis C virus dynamics and cellular gene expression in uPA‐SCID chimeric mice with humanized livers during intravenous silibinin monotherapy, DOI:10.1111/jvh.12551 .